(untitled) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2023)
This study aims to prove: (1) The effect of Regional Original Income on Capital Expenditure in the Special Region of Yogyakarta Province. (2) The effect of the General Allocation Fund on Capital Expenditure in the Special Region of Yogyakarta Province. (3) The influence of the Special Allocation Fund on Capital Expenditure in the Province of the Special Region of Yogyakarta. (4) The Effect of Revenue Sharing Funds on Capital Expenditures in the Province of the Special Region of Yogyakarta. (5) The effect of Regional Original Revenue, General Allocation Fund, Special Allocation Fund and Revenue Sharing Fund together on Capital Expenditure in the Special Region of Yogyakarta Province. Methods of data collection using documentation techniques. The object of this research is the Financial Statements of the Special Region of Yogyakarta in 2017- 2020. The analytical methods used are: Classical assumption test, multiple linear analysis, hypothesis testing, coefficient of determination test. The results of the study show that: (1) Regional Original Income has a significant effect on Capital Expenditures. (2) General Allocation Fund has no significant effect on Capital Expenditure. (3) The Special Allocation Fund has a significant effect on Capital Expenditures. (4) Profit Sharing Funds have no significant effect on Capital Expenditures. (5) Regional Original Revenue, General Allocation Fund, Special Allocation Fund and Revenue Sharing Fund together have a significant effect on Capital Expenditure.